Pengembangan Sistem Informasi Pendaftaran Siswa Sekolah Dasar Secara Online dengan Metode Waterfall - Muhammad Satria Mubin; Briyan Chairullah; Muhammad David Adrilyan; Errissya Rasywir (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The system used at SDN 01 Tanjung Jabung Timur is currently in the process of admitting new students, which is still done manually. The high interest of prospective new students to register at SDN 01 Tanjung Jabung Timur made the admissions committee have difficulty handling it, resulting in a buildup of registrants at the peak of registration, while the number of committees serving was limited. The purpose of this research is to design a website-based new student registration system for easy access from outside the area of ​​students at SDN 01 Tanjung Jabung Timur and to make it easier for prospective students to register at SDN 01 Tanjung Jabung Timur students. System development is carried out using the waterfall model, because the application is easy and systematic. The program is designed using UML (United Model Language) diagrams such as Use Case Diagrams, Activity Diagrams, and Class Diagrams to design an online registration system. This research resulted in a web-based Admissions information system at SDN 01 Tanjung Jabung Timur which was built using the PHP programming language with the Laravel framework and the PhpMyAdmin database and with this application it also helps the school in managing new student data